Laws and Regulations Related to Foreign Direct Investment in Mozambique - JLA Advogados (Agency for Promotion of Investment and Exports (APIEX), 2017)
After becoming an independent State, Mozambique was plagued by a long and severe civil war, which ultimately resulted in an economic collapse led by the lack of investment, nationalization of privately owned industries, as well as widespread food shortage. The 1992 peace agreement marked the transition from civil war to peace, culminating in the country’s first democratic elections of 1994 and the emergence of the Front for the Liberation of Mozambique (Frelimo) as the dominant political force in the country; a fact that still holds true today. In 1993 the Mozambican Government approved the Investment Act to foster and promote both national and foreign investmentsin the country, granting various benefits and incentives, which include: tax and custom duties exemptions, free remittance of funds, and the possibility of hiring more foreign workers than those permitted by law. These incentives vary according to the economic and industrial activity pursued and the region of implementation of the project. Mozambique’s rapid economic expansion over the past decades has had only a moderate impact on poverty reduction, and the geographical distribution of poverty remains largely unchanged. Despite the recent discoveries of natural resources in the oil & gas sectors, Mozambique is undergoing serious economic and political crisis and needs to improve its social indicators. The country ranked 178th out of 187 countries in the most recent Human Development Index (HDI). The adult literacy rate is 56% (fifty six percent), and average life expectancy at birth is just 50,3 (fifty point three) years. In January 2015, after the 5th (fifth) peaceful election process, Mozambique’s fourth president came into office Mr. Filipe Nyusi. His party also secured a strong majority in the parliament, with 144 seats out of 250 in total.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais